Development of robust metric based on cumulative electrical power for electromechanical impedance based structural health monitoring. (16th October 2020) - Soman, Rohan; Singh, Shishir Kumar; Wandowski, Tomasz; Malinowski, Pawel
Abstract: Electromechanical impedance (EMI) based techniques have been proposed for structural health monitoring due to their sensitivity to low levels of damage. Most of the work in the EMI technique depends on the change in the admittance signature of the structure in the healthy and damaged state. Several metrics have been proposed to quantify this difference in the signature. Most common being root-mean square difference (RMSD), mean absolute percentage deviation, correlation coefficient etc. As the admittance signatures has several troughs and peaks, the statistical metrics are not robust and often show false detection due to ambient changes and measurement noise. Thus, this paper proposes a novel index for the damage detection using the EMI technique based on the cumulative electrical power. The frequency v/s resistance or conductance plot is used for calculating the normalized cumulative electrical power (NCP) of the system. The NCP curve is a monotonically increasing function and hence robust for statistical comparison. The cumulative power curve is then used to develop three different indices comparing the amplitude difference (RMSD of the NCP curves), difference in the area under the NCP curve as well as the modified Frechet distance between the NCP curves. The performance of these indices are compared with the RMSD index which has been commonly used. The comparison is carried out on four different structures and show very encouraging results. In addition to the experimental validation, sensitivity studies have been carried out on an analytical signal. It is seen that the Frechet distance based index is a robust indicator for damage detection and minimizes the false detection under variety of conditions affecting the EMI signature.